Managing service: using technology to create value - Mark M. Davis (McGraw Hill Companies, 2003)
File dalam bentuk PDF, Gambar, Htm (Internet), Word dll; Isi: Chapters, Conversion, Costum, DACD-Demo, DCAL, Error, Gallery, Learning_sites, Macros, References, Sharewere, Tmp_sym, dll; Judul Dalam Kemasan.